INJURY LAW SETTLEMENT PROMISE OF RENTING OF FOUR WHEEL MOTOR VEHICLE IN SUKAJADI DISTRICT, PEKANBARU CITY Yeni Triana - Yeni Triana; Dedy Felandy (Prosiding Seminar Nasional Pakar, 2019)
The purpose of this study was to analyze leasing agreements for car vehicles, which were not carried out by the parties in accordance with what was agreed in the contents of the agreement, in Sukajadi District, Pekanbaru City. So that what has been agreed upon by both parties can be realized as agreed. With all the risks contained in the contents of the agreement, it must be carried out by both parties in the leasing agreement of the vehicle.The target to be achieved in this research activity is to increase understanding of both parties who rent a car vehicle, as well as those who rent the vehicle car, regarding the agreement of the lease agreement, if both parties do not carry out the contents of the lease agreement. and for researchers themselves make a very important contribution to the legal problems faced by the community, especially regarding leasing agreements.The research method is with sociological law, the research location is a rental service company located in Sukajadi Subdistrict, Pekanbaru City, polluting and sampling the parties of the leaseholders, consumers, with verbal interview methods in order to find information as processed data of this research.Outputs are produced according to the plan of activity for proposers in the form of scientific articles, and study learning materials for students.